Wegeners Granulomatosis with Peripheral Eosinophilia in a Young Adult Patient (Journal of Medicine, 2014)
Wegeners granulomatosis is a rare autoimmue disease with multi-system involvement that manifests as granulomatous vasculitic lesions, mainly involving the upper respiratory tract, lower respiratory tract and kidney. We present a case in a young adult male patient presenting with complaints of epistaxis, cough and hemoptysis who was diagnosed as Wegeners granulomatosiswith peripheral eosinophilia on the basis of chest x-ray and CT Chest and pathological confirmation by high level of serum cytoplasmic antineutrophil cytoplasmic antibody.DOI: http://dx.doi.org/10.3329/jom.v14i2.19689 J Medicine 2013, 14(2): 204-206